2021
DOI: 10.1111/ijfs.15115
|View full text |Cite
|
Sign up to set email alerts
|

Variation of mineral contents with nutritional interest in a collection of Solanum tuberosum group Phureja tubers

Abstract: Summary Colombia has a biodiversity centre of diploid potatoes located at south of the country. This study evaluated the amounts of potassium (K), calcium (Ca), iron (Fe) and zinc (Zn) in a biodiversity panel of potato tubers, constituting native cultivars, accessions of the Working Collection of Potato Breeding Program at the Universidad Nacional de Colombia (CCC) and commercial cultivars. The highest quantity of minerals found were as follows: 34 333 ± 4509 mg K kg−1 potato dry weight (DW; CCC112), 1965 ± 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Other important nutrients in potatoes include minerals and vitamins such as potassium, magnesium, vitamin C as well as vitamin B6, among others [10,11]. Potatoes are a reliable source of ascorbic acid -ranged from to 5.8 to 21 mg of vitamin C per 100 g tuber on a fresh weight (FW) basis-, however several studies have reported changes in the content of vitamin C in potato tubers depending on variety [12,13]. Potato flesh color ranged from white to dark yellow cultivars are the most common, a recent review showed that the total carotenoids content of tubers is influenced by location, season, genotype, and their interactions, with values between 5 and 10 mg kg −1 FW of total carotenoids, for white-fleshed potatoes, to over 100 mg kg −1 FW of total carotenoids for darkyellow potatoes [14].…”
Section: Cultivated Potato and Red-purple Fleshed Potatoesmentioning
confidence: 99%
“…Other important nutrients in potatoes include minerals and vitamins such as potassium, magnesium, vitamin C as well as vitamin B6, among others [10,11]. Potatoes are a reliable source of ascorbic acid -ranged from to 5.8 to 21 mg of vitamin C per 100 g tuber on a fresh weight (FW) basis-, however several studies have reported changes in the content of vitamin C in potato tubers depending on variety [12,13]. Potato flesh color ranged from white to dark yellow cultivars are the most common, a recent review showed that the total carotenoids content of tubers is influenced by location, season, genotype, and their interactions, with values between 5 and 10 mg kg −1 FW of total carotenoids, for white-fleshed potatoes, to over 100 mg kg −1 FW of total carotenoids for darkyellow potatoes [14].…”
Section: Cultivated Potato and Red-purple Fleshed Potatoesmentioning
confidence: 99%